Ideologi Pancasila Dalam Menghadapi Pemikiran Radikalisme Pada Mahasiswa UNIMED - Patricia Angelica Br. Nadapdap; Nurima Nurima; Tamara Angelsky M; Maria Angel; Reni Romaito Hsb; Milandania Milandania (LPPM Politeknik Pratama, 2023)
Pancasila ideology has a very important role in dealing with radicalism among students. Radical thinking is a serious challenge for students who are the nation's next generation. This research aims to find out students' insights regarding radicalism and explain how Pancasila can be a guide in facing the challenges of radicalism in students.This research was conducted using qualitative methods. Researchers collected data by triangulation and inductive data analysis. This data was collected by approaching respondents by filling out questionnaires for state university students. This research used a questionnaire by taking 100 respondents who were UNIMED students. The questionnaire is open for 2 weeks in September-October 2023. This research questionnaire contains 10 questions related to knowledge and incidents of radicalism.From the results of the research carried out, it can be concluded that Medan State University students already know and understand what radicalism is. The majority of students were exposed to radicalism when they were in college and when they were in high school. Students understand in depth the problem of radicalism that occurs in the environment around campus. Only a few students have a radical nature and carry out radical actions against each other.